CLINICAL CARE PATHWAYS FOR MENTAL HEALTH CARE: A FEASIBILITY STUDY (Forum for Linguistic Studies, 2024)
Introduction: World Health Organization reported that mental and behavioural disorders account for about 12 percent of the global burden of diseases. In this study, researcher evaluated the efficacy for clinical care pathways for mental health care admitted ina tertiary care hospital in Wardha,India.Objective of the study is : To evaluate the feasibility of clinical care pathways for mental health care. Methodology: Research design adopted was one group pre test post test design. Sample size taken for the study was 10 samples. Populations of the study are the patients with common mental disorders Intervention implemented for the study was GMHAT-PC critical care pathways. Setting taken was Psychiatric unit of a tertiary care hospital in central India.  Result: The result shows Quality of care among patients with mental disorders improved remarkably after the implementation of clinical care pathways (p=0.05) and they expressed moderate level of satisfaction. GMHAT-PC critical care pathways checklist score significantly improve among nurses after training and continued to improve at every 15th day in three phases.Conclusion: Implementation of critical care pathways is feasible and accepted by nurses working in psychiatric care units. Minimum training in GMHAT-PC clinical care pathways improved the patient satisfaction and quality of care to patients with common mental disorders.